A novel sandwich-type photoelectrochemical sensor for SCCA detection based on Ag2S-sensitized BiOI matrix and AucorePdshell nanoflower label for signal amplification. (3rd September 2018) - Bao, Chunzhu; Wang, Chuanlei; Fan, Dawei; Ma, Hongmin; Hu, Lihua; Fan, Yingju; Wei, Qin
Abstract : Signal amplification was fulfilled for the interaction between BiOI/Ag2 S and Auc Pds . Abstract : A novel sandwich-type photoelectrochemical (PEC) sensor for SCCA detection, based on a Ag2 S-sensitized BiOI matrix and a Aucore Pdshell (Auc Pds ) nanoflower label for signal amplification, was constructed for the ultrasensitive detection of the squamous cell carcinoma antigen (SCCA). By an in situ growth method, Ag2 S was modified on the electrode coated with BiOI to obtain the BiOI/Ag2 S composite. The BiOI/Ag2 S matrix possesses an excellent photocurrent signal that is 90 times that of pure BiOI. The core–shell nanoflower-structured Auc Pds was utilized as a label to anchor secondary antibodies (Auc Pds @Ab2 ) to construct the ultrasensitive PEC sensor. The Auc Pds nanoflower can compete with the BiOI/Ag2 S matrix for the absorption of visible-light to inhibit the electron transfer and then weaken the photocurrent signal of the BiOI/Ag2 S matrix. After modification with the Auc Pds @Ab2 conjugate, the PEC signal was further reduced due to the efficient energy transfer process between the BiOI/Ag2 S matrix and Auc Pds . Based on the above two influencing factors, the signal amplification strategy was fulfilled. Moreover, on the basis of specific recognition between antigen and antibody, an ultrasensitive PEC sensor for SCCA detection was successfully fabricated. On increasing the logarithm of the SCCA concentration in the range from 0.01 pg mL −1 to 100 ng mL −1, the photocurrent signals were linearly reduced and the detection limit was 1.6 fg mL −1 . The fabricated sandwich-type PEC sensor has excellent sensitivity and distinguished stability, which are indicative of promising applications in clinical diagnoses, sensors and PEC analysis.